Relevansi Maqasid al-Shari’ah dalam Penyelesaian Masalah Hukum Kontemporer - Dayan Fithoroini (Justicia Religia, 2025)
The rapid social, technological, and economic changes of the past two decades have placed legal systems, including Islamic law, under significant methodological challenges. Phenomena such as the digitalization of transactions, the development of fintech, medical bioethics issues, and the complexity of public governance demand a legal approach that is not only textual but also able to capture the normative objectives and fundamental values intended to achieve sharia. In this context, the maqasid al-shari'ah is re-emerged to analyze its relevance as a normative approach in resolving various contemporary Islamic legal issues. Using library research methods, this study examines classical and modern literature to identify the position, function, and implementation of Maqasid al-shari'ah in responding to issues such as digital transactions, reproductive health, and social governance. The findings indicate that Maqasid al-shari'ah provides a flexible, adaptive, and welfare-oriented framework, thus serving as a guideline for realizing contextual, progressive, and solution-oriented Islamic law. In conclusion, the maqasid approach is highly relevant for the development of Islamic law in the modern era.